Malacological news from the Czech and Slovak Republics in 2023 - Čejka, Tomáš; Beran, Luboš; Adamcová, Tereza; Bronišová, Veronika; Coufal, Radovan; Čiliak, Marek; Drvotová, Magda; Horáčková, Jitka; Horsáková, Veronika; Juřičková, Lucie; Kocurková, Alena; Korábek, Ondřej; et al. (Malacologica Bohemoslovaca, 2024)
This paper presents important faunistic records conducted in the Czech and Slovak Republics during 2023. We also include records generated before 2023, which have yet to be published, mainly because their correct identification was unavailable earlier. In a separate section we present records of unintentionally introduced species, reported for the first time for the countries from greenhouses (Dryachloa dauca and Guppya gundlachii). The first outdoor colony of Melanoides tuberculata was found in a stream artificially heated by wastewater from the Dukovany nuclear power plant and Planorbella duryi found in a brook with thermal water flowing from the Sliač spa. Records of native species include findings of protected and rare species (e.g., Aplexa hypnorum, Ladislavella occulta, Daudebardia brevipes, and Theodoxus danubialis), but also still poorly known species (Ampullaceana lagotis and Pyramidula saxatilis). During 2023, many new records were made for non-native and currently spreading species as for example Clathrocaspia knipowitschii, Corbicula fluminea, Hygromia cinctella, Krynickillus melanocephalus, Sinanodonta woodiana, and Tandonia kusceri.